(3JbfjGJ GdGJUGd Hjf Refjf (B/s - (3GdHcQj, EjGO TGcQs ((3GdCQOf (B:s (3OGQ GdTQhb ddfTQ h GdJhRjY ,s, 2003)
(3Jcef gPG GdcJGH ef NdGd JfGhd ehVhYGJg dJbfjGJ GdGJUGd GdJbdjOjI h GdMOjKI YHQ Refjf GhYUQjf GfLRJ aj YbhO GdRef GdGhd (B((3Ref GdGNJQGY(B) (3eLehYI ef GdJbfjGJ GdbdjOjI aj eLGd hSGF GdGJUGd h ef Ke JbOe gPg GdJbfjGJ aj GdRef GddGMb (B((3Ref JWhQ(B) (3h aj ebOeJgG GdMGShH h GdGfJQfJ h GdJdaRjhf GdQbej h GbeGQ GdHK GdeHGTQ h GSJNOGe JbfjI GdeYdheGJ aj GdHMhK GdYdejI h GdJj dgG YdGbI eHGTQI HMjGI GdEfSGf GdeYGUQ GdYedjIs
(3HHdjhZQGajG (B: (3U(B.177-180s
Keywords: (3GdEPGYIs; (3GdEfJQfJs; (3GdJdjaRjhfs; (3GdGJUGds